2006
DOI: 10.5334/pb-46-3-199
|View full text |Cite
|
Sign up to set email alerts
|

Does it Matter to be Pictured from Below?

Abstract: Does the way in which a scene is viewed influence the interpretation of the role of the characters that appear in it, and does narrative context influence sensitivity to camera angle? In the linear conditions of the present study, each of 3 stories consisted of a sequence of 5 pictures. Pictures 2 and 3 introduced the 2 characters with either a high-angle, an eye-level, or a low-angle shot. In the random conditions, the 5 pictures were rearranged into a random order. Immediately after viewing each story, the 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 9 publications
(15 reference statements)
0
7
0
Order By: Relevance
“…Kraft found that low angles produced an image of strength, action, and superiority; eye-level shots produced parity; and high angles created impressions of weakness, passivity, and insignificance. In a similar design, Sevenants and d’Ydewalle (2006) showed that a low-angle shot elicited significantly more potency (which was also found by Mandell & Shaw, 1973; but not by Meridian, 1987).…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…Kraft found that low angles produced an image of strength, action, and superiority; eye-level shots produced parity; and high angles created impressions of weakness, passivity, and insignificance. In a similar design, Sevenants and d’Ydewalle (2006) showed that a low-angle shot elicited significantly more potency (which was also found by Mandell & Shaw, 1973; but not by Meridian, 1987).…”
Section: Introductionmentioning
confidence: 85%
“…Two studies have looked at the interaction of narrative and camera angle (Kraft, 1987;Sevenants & d'Ydewalle, 2006). Kraft (1987) showed participants six short-four-picture stories, for example, ''The Encounter'' (two dogs greet each other) or ''The Dented Car'' (a man and a woman are involved in a mild car accident).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As conceptualized by film theorists, camera angle has a linear effect according to which straight angles are neutral, low angles emphasize power, and high angles indicate weakness (Giannetti, 1999). Such linearity has been supported by multiple experimental studies with high and low angles exhibiting opposing effects on power (Giessner et al, 2011; Kraft, 1987; Mandell & Shaw, 1973; Sevenants & d’Ydewalle, 2006), as well as other dimensions such as credibility (Avery & Long, 1976; Tiemens, 1970) and favorability (Meyers-Levy & Peracchio, 1992). However, there is also evidence to the contrary, with some studies have found that both high and low angles decrease perceived trustworthiness (Baranowski & Hecht, 2018), and that the pattern is rather disparate and non-linear when considering the degree of angle (Kepplinger & Donsbach, 1987).…”
Section: Literature Reviewmentioning
confidence: 82%
“…However, the question of how form interacts with content remains largely unexplored because the stimuli employed in previous experiments have been of limited variability. This is particularly true for camera angle studies, where stimuli range from monologues, lectures, or newscasts (Avery & Long, 1976; Baranowski & Hecht, 2018; Mandell & Shaw, 1973; Reeves et al, 1992; Tiemens, 1970), to representations of everyday events (Kraft, 1987; Sevenants & d’Ydewalle, 2006), and images of objects (Meyers-Levy & Peracchio, 1992). Although some studies on camera distance have used more emotionally complex stimuli (Bálint et al, 2020; Canini et al, 2011; Mutz, 2007), they have typically used few or single message designs, with the exception of Canini et al (2011), who did include messages from a larger emotional spectrum but found a reversed relationship between closeness and emotional arousal.…”
Section: Literature Reviewmentioning
confidence: 99%